Modelling the time dependent behaviour of anisotropic soft clay using non-stationary flow surface theory - Nguyen, Dinh Hung (2021)
Prediction of the long-term deformation of a soft clay under different loading conditions has been a challenging task for geotechnical engineering since the time dependency of soft clay is a complex matter. This topic has attracted the attention of researchers for many decades. An insight into a scenario related to the time dependency of soft clay is a significant pathway to provide the best solution in geotechnical design for geo-structures constructed on soft ground. This thesis is made an attempt to study the time dependent behaviour of soft clay and proposed an advanced time dependent constitutive model, namely NSFS-SCLAY1S model which can capture the significant advanced features of soft clay regarding fabric anisotropy, destructuration of inter-particle bonding and time dependency. The model was developed based on the non-stationary flow surface theory (NSFS) which was proposed by Perzyna in 1964. The NSFS theory is a further development of inviscid elasto-plastic theory, in which a time variable parameter is introduced in the yield surface equation to obtain the simultaneous description of strain hardening and the effect of time. This means that the yield surface can change at any moment. The inherent framework from the classical elasto-plastic theory is used in determining the viscoplastic strain, leading to the simplification of the numerical solution. The preference of NSFS theory in this research is due to the limitation of overstress-based consititutive models of describing properly the creep behaviour of soft clay. The proposed NSFS-SCALY1S model, in contrast, is capable of capturing the strain rate effects and creep response of soft clay. In particular, it is able to simulate tertiary creep response, which is an important phase of creep behaviour which leads to creep failure of soft soil deposits.